Prenatal profile of Pallister‐Killian syndrome: Retrospective analysis of 114 pregnancies, literature review and approach to prenatal diagnosis. Issue 12 (5th October 2018) - Salzano, E; Raible, SE; Kaur, M; Wilkens, A; Sperti, G; Tilton, RK; Bettini, LR; Rocca, A; Cocchi, G; Selicorni, A; Conlin, LK; McEldrew, D; et al.
Abstract : Pallister‐Killian syndrome (PKS) is a tissue limited mosaic disorder, characterized by variable degrees of neurodevelopmental delay and intellectual disability, typical craniofacial findings, skin pigmentation anomalies and multiple congenital malformations. The wide phenotypic spectrum of PKS in conjunction with the mosaic distribution of the i(12p) makes PKS an underdiagnosed disorder. Recognition of prenatal findings that should raise a suspicion of PKS is complicated by the fragmentation of data currently available in the literature and challenges in diagnosing a mosaic diagnosis on prenatal testing. Ultrasound anomalies, especially congenital diaphragmatic hernia, congenital heart defects, and rhizomelic limb shortening, have been related to PKS, but they are singularly not specific and are not present in all affected fetuses. We have combined prenatal data from 86 previously published reports and from our cohort of 114 PKS probands (retrospectively reviewed). Summarizing this data we have defined a prenatal growth profile and identified markers of perinatal outcome which collectively provide guidelines for early recognition of the distinctive prenatal profile and consideration of a diagnosis of PKS as well as for management and genetic counseling.